Fabry disease defined: baseline clinical manifestations of 366 patients in the Fabry Outcome Survey - Mehta, Atul B.; Ricci, R.; Widmer, U.; Dehout, F.; Lorenzo, A. Garcia de; Kampmann, Christoph; Linhart, A.; Sunder-Plassmann, Gere; Ries, Markus; Beck, Michael (European journal of clinical investigation, 2004)
Background Fabry disease is a rare X-linked disorder caused by deficient activity of the lysosomal enzyme α-galactosidase A. Progressive accumulation of the substrate globotriaosylceramide in cells throughout the body leads to major organ failure and premature death. In response to the recent introduction of enzyme replacement therapy, the Fabry Outcome Survey (FOS) was established to pool data from European clinics on the natural history of this little-known disease and to monitor the long-term efficacy and safety of treatment. This paper presents the first analysis of the FOS database and provides essential baseline data against which the effects of enzyme replacement can be measured. Design Baseline data from a cohort of 366 patients from 11 European countries were analysed in terms of demography and clinical manifestations of Fabry disease. Results Misdiagnosis of Fabry disease is common, and the mean delay from onset of symptoms to correct diagnosis was 13·7 and 16·3 years in males and females, respectively. Although previously thought to have serious manifestations only in hemizygous men, the FOS database has confirmed that females heterozygous for Fabry disease are similarly affected. Furthermore, signs and symptoms of Fabry disease may be present from early childhood. Conclusions With the advent of enzyme replacement therapy, it is important that general practitioners and physicians in a range of specialties recognize the signs and symptoms of Fabry disease so that effective treatment can be given. Baseline data from FOS demonstrate that enzyme replacement therapy should not be restricted to hemizygous men, but should be considered for both heterozygous females and children.
Gesehen am 16.05.2019